Axial impact on carbon fiber tubes: numerical and experimental study. - Ataabadi, Pouria Bahrami (2019)
Carbon Fiber-Reinforced Plastics, CFRPs, have been widely used in the industry due to their high specific strength and stiffness ratios as well as good crushing performance when used as energy absorbers. Here, an experimental characterization of the crushing mechanism of tubular carbon fiber/epoxy absorbers is described in details, side by side with a finite element, FE, simulation of these components under compression. In the experimental study, CFRP tubes with two different stacking sequences, cross-ply and angle-ply, underwent axial quasi-static and impact in order to investigate possible effects of loading rate, stacking sequence and cross-section shape on the energy absorption capacity of the tubes. The experimental results were used to support the development of the finite element model of the composite parts under axial impact. Using Abaqus/Explicit code, a multi-layer model of laminated tube was conceived. Concentric layers of conventional shell element (S4R), in contrast to the extensive use of continuum elements, were adopted. A simple tying technique based on Continuum Damage Mechanics (CDM) was used to tie adjacent composite layers. The implementation of this bonding technique is more straightforward when comparing with the cohesive zone modes, requiring fewer mechanical properties as input. The results obtained from the numerical model agreed well with the experimental campaign, encouraging the use of the advanced finite element model developed here.